E-GOVERNANCE AND CITIZEN PARTICIPATION: A NEW PARADIGM FOR TRANSPARENT ADMINISTRATION - Chachane, Harsha (International Journal of Engineering Technologies and Management Research, 2024)
E-governance represents a transformative shift in administrative systems, redefining how governments engage with citizens through technology-driven transparency and participation. This paper explores how digital governance initiatives enhance administrative efficiency, citizen engagement, and accountability in developing democracies. Using a mixed-method approach across selected case studies (India, Brazil, and Kenya), this study analyzes the relationship between digital participation tools and policy transparency. Hypothetical findings reveal that increased citizen interaction through e-portals, mobile apps, and open data systems directly correlates with improved public trust and administrative responsiveness. Despite challenges such as digital divide, cybersecurity, and bureaucratic inertia, e-governance emerges as a key driver of participatory democracy. The study concludes that integrating ICTs with inclusive policy design and continuous citizen feedback mechanisms can reshape public administration into a transparent, people-centric system.